Are the 'Hidden Unemployed' Unemployed? - Elliott, L; Dockery, A.M. (My University, 2006)
This paper compares mutually exclusive labour market states to determine whether discouraged jobseekers are more akin to the unemployed or others not in labour force. Data from four waves of the longitudinal Household, Income and Labour Dynamics in Australia survey are used to determine similarities in the behavioural characteristics and transition dynamics of the labour force states, with a focus on comparing discouraged jobseekers with the other non-employed states. Evidence from a range of indicators, including measures of financial circumstances, subjective wellbeing and reservation wages, rejects the notion that discouraged jobseekers represent a group of ‘hardcore unemployed’ who are, on average, experiencing greater hardship from their state of joblessness than the conventionally defined unemployed. Analysis of transitions between labour force states also reveals that discouraged jobseekers are behaviourally similar to others classified as not in the labour force rather than the unemployed. Consequently, the results support the present official definitions of participation and unemployment.
Centre for Labour Market Research, Curtin University of Technology, Discussion Paper Series
Keywords: Employment -- Labour force status and attachment; Employment; Employment -- Unemployment; Labour market; Employment and unemployment